Emerging and reemerging zoonoses and their importance for animal health and production - Zanella, Janice Reis Ciacci (Pesquisa Agropecuaria Brasileira, 2016)
The factors for disease emergence or reemergence are little known and understood, but the main one is the expansion of the human population. Other factors include climate change, globalization, and intensification of animal production. This is disturbing, given that 75% of emerging or reemerging human diseases of the last century are zoonoses, that is, animal diseases, which, besides causing human and animal fatalities, affect the economy of countries. It is estimated that the impact of animal diseases exceeds 20% of the losses in animal production worldwide. Brazil is a major agricultural producer and has most of its territory in the tropical region, harboring the greatest environmental biodiversity of the globe. Studies have pointed the Amazon region as a hot spot where diseases have emerged or will emerge. In this context, the formation of a cooperation network with strategic actions for monitoring, research, communication, and training is recommended. It is essential to foster partnerships in the areas of health, agriculture, and environment for a prompt national and global response. The objective of this work was to address the main factors involved in the emergence or reemergence of zoonoses, as well as future threats and the strategic importance of Brazilian research and surveillance.